1447Gastric histopathology by Helicobacter pylori cagA status in Arctic Canada. (2nd September 2021) - Cromarty, Taylor; Quilty, Douglas; Assi, Ali; Girgis, Safwat; van Zanten, Sander Veldhuyzen; Goodman, Karen; ,
Abstract: Background: Our community-driven projects address concerns of Canadian Arctic Indigenous communities about Helicobacter pylori ( Hp ) infection, responsible for elevated gastric cancer mortality in the region. Community research partners wished to learn whether bacterial characteristics determine severity of Hp -related disease in their communities. We aimed to describe gastric histopathology by cagA genotype of Hp isolated from residents of 7 Indigenous communities in the Northwest Territories and Yukon. Methods: Participants underwent gastroscopy with 5-6 biopsies taken for histopathological assessment and 2 biopsies taken for tissue culture during 2008-2017. We used multiple PCR reactions and DNA sequence analysis to classify Hp genotypes as cagA+ or cagA -. A single pathologist used the updated Sydney classification system to grade severity of 5 gastric pathology outcomes: Hp density; chronic gastritis; active gastritis; atrophy; and intestinal metaplasia. We estimated prevalence of each outcome with 95% confidence intervals (CI) by gastric subsite and cagA status. Results: Of 262 Hp isolates assessed, 142 (54%) were cagA +. Prevalence of moderate-high Hp density, severe chronic gastritis, moderate-severe active gastritis, atrophy, and metaplasia were (%[CI]): respectively, 78[70-85], 44[36-53], 65[56-72], 55[46-63], 25[18-33] in cagA + participants and 61[52-70], 35[27-44], 31[23-40], 32[23-41], 8[4-15] in cagA - participants. cagA + participants had higher prevalence of all outcomes in antrum and corpus. Conclusion: Hp -infected Indigenous residents of Arctic Canada who harbored cagA -positive strains had higher prevalence of more severe gastric pathology than those with cagA -negative strains. Key messages: Community-driven research answers questions posed by those who bear the disease burden.